"I Didn't Feel Like I Was a Person Anymore": Realigning Full Adult Personhood after Ostomy Surgery. (30th April 2014) - Ramirez, Michelle; Altschuler, Andrea; McMullen, Carmit; Grant, Marcia; Hornbrook, Mark; Krouse, Robert
<x xml:space="preserve">Abstract</x> Colorectal cancer (CRC) is the third most common cancer in the United States. For some CRC patients, cancer treatment involves creating a permanent or temporary intestinal ostomy. Having an ostomy often results in complex social and physical concerns—including unpredictable and at times publicly noticeable bowel output. In this article, we discuss findings from 30 in‐depth interviews with female CRC survivors with ostomies in the western United States. We highlight how having an ostomy disrupts culturally sanctioned practices of continence that mark the attainment of full‐adult personhood. We discuss how survivors reclaim a sense of full personhood after ostomy surgery through a process of realignment that entails both learning how to manage ostomy equipment to conceal bowel activity and reappraising their illness and suffering. We suggest that the anthropological categories of personhood and personhood realignment be incorporated into research and interventions aimed at increasing support among cancer survivors living with bodily impairments.